Effectiveness of Controlling Agricultural Land Conversion in the Puncak Tourism Area of Cisarua Subdistrict by the Bogor Regency National Land Agency from a Spatial Planning Law Perspective - Putri Kastiady, Salvia Salsabila (Indonesian Journal of Agrarian Law, 2026)
The development of tourism in the Puncak area of Cisarua District has led to an increase in the conversion of agricultural land into residential areas and villas, which has the potential to conflict with the Regional Spatial Plan (RTRW). This study aims to analyze the effectiveness of controlling the conversion of agricultural land in the Puncak area from a spatial planning law perspective and to identify the factors causing land use inconsistencies. The method used is juridical-empirical with the support of spatial analysis through the technique of analyzing land use maps for 2020 and 2025 based on Google Earth imagery compared with the Bogor Regency RTRW (Local Regulation Number 1 of 2024). The results of the study show that there has been significant land conversion in agricultural and buffer areas, with a total area of non-compliance reaching 7,803 hectares. This reflects weak preventive supervision, limited post-grant control, and suboptimal integration of land and spatial planning data. This study recommends strengthening institutional coordination, integrating data systems, and tightening spatial planning compliance verification to support sustainable land management.